Penguatan Ekonomi Masyarakat melalui Pembangunan Desa Wisata: Studi di Wana Wisata Sumber Biru, Wonosalam, Jombang dalam Perspektif Komunikasi Sosial dan Politik Media - Muchlis, Muchlis (Jurnal Ilmu Komunikasi, 2024)
This research discusses strategies for strengthening the community's economy through the development of the tourism village called Wana Wisata Sumber Biru in Wonomerto Village, Wonosalam District, Jombang Regency, especially related to forms of social and political communication as well as media communication. Using qualitative methods, the results of this study show that lifting and strengthening the community economy of the tourist village relies on community participation where funds for the development of the Sumber Biru Tourism Area are mostly sourced from community self-help and assistance from village-owned enterprises. Regarding forms of social and political communication, the managers of the Tourism Village 'Wana Wisata Sumber Biru' conduct intensive political communication with policy-makers, both at the sub-district, sub-district, and district levels. Meanwhile, related to media communication, the management strives to establish good relations with the mass media to distribute information to the wider community regarding the existence of Wana Wisata Sumber Biru as an alternative tourist destination that is worth visiting